Science Literacy Ability with The Discovery Learning Model on Thermochemistry Subject Material - Linda; Abdullah; Albeta, Sri Wilda (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This research is motivated by students’ inability to connect the scientific knowledge they learn to everyday phenomena related to chemistry, particularly thermochemistry. This problem stems from a lack of student motivation and interest in chemistry learning, partly due to the extensive scope of the chemistry material. The learning process at State Senior High School 15 Pekanbaru uses the lecture method and tends to memorize concepts and theories. During the learning process, teachers have not yet implemented scientific literacy in explaining the material and relating it to everyday life. However, low scientific literacy makes students less able to find information related to problems, thus making them reluctant to do so. The research was conducted in grade XI of State Senior High School 15 Pekanbaru in the odd semester of the 2024/2025 academic year. The research design used an equivalent pretest-posttest group design with two classes: a control class and an experimental class. The population of this study consisted of classes XI A, XI B, XI C, XI D, and XI E. The sample used was Class XI A as the experimental class, which was given the discovery learning model, while Class XI B as the control class was not given the discovery learning model. Data collection was conducted using pretest scores as initial data for normality and homogeneity tests, and the difference between pretest and posttest scores for hypothesis testing. The results of the hypothesis test calculation using the t-test obtained t count > t table, i.e., with df, thus the research hypothesis was accepted. The application of the discovery learning model can be recommended as an alternative to improve students’ scientific literacy skills, especially in thermochemistry.